Biological characterization and in vitro fungicide screening of a new pathogen of basal stem rot of Schisandra chinensis in Jilin Province, China - Tian, Taiping; Wang, Mengqi; Zhu, Jingmeng; Sun, Yining; Ma, Mingjie; Liu, Guoliang; Wang, Jinshuo; Zhao, Bing; Yan, Yiping; Wang, Yue; Wang, Yanli; Li, Changyu; et al. (Frontiers in Microbiology, 2025)
IntroductionSchisandra chinensis (Turcz.) Baill. is a widely cultivated medicinal plant with significant economic value and serves as a major component of specialty agriculture in Jilin Province, China. In 2024, a novel basal stem rot disease was observed in Latai Village, Liudaogou Town, Linjiang City, Jilin Province, posing a potential threat to local production.MethodsField symptoms were characterized by stem-base necrosis, vascular browning, wilting, and plant death, often accompanied by soft rot under high humidity. The causal pathogen was isolated and identified through morphological observation and sequencing of ITS, β-tubulin (TUB), and TEF1-α genes. Pathogenicity was confirmed via Koch’s postulates on detached stems, seedlings, whole plants, and tissue-cultured plantlets. Biological characteristics were evaluated under different media, temperatures, light conditions, pH levels, and carbon/nitrogen sources. Additionally, seven fungicides (three chemical and four botanical) were tested for inhibitory activity in vitro.ResultsThe pathogen was identified as Ilyonectria robusta, marking the first global report of this species causing basal stem rot on S. chinensis. Optimal growth conditions included CDA or CMA media, 25°C, continuous darkness, and pH 7. Sodium nitrate and lactose were the most favorable nitrogen and carbon sources, respectively. Among the fungicides tested, 98% fluazinam showed the strongest inhibitory effect with an EC₅₀ value of 5.658 mg/L.DiscussionThis study confirms I. robusta as a novel and virulent pathogen of S. chinensis in Jilin Province. The findings provide foundational data on its biology and pathogenicity and identify fluazinam as a promising candidate for integrated management of basal stem rot disease.